What is a healthy dating relationship and what helps it get there? Perceptions of Chilean adolescents from a gender and inclusivity perspective - Zulic-Agramunt, Christianne; Poo-Figueroa, Ana; Gatica-Bahamonde, Gabriel; Salazar, Nicolás; Saldana, Andrea; Carter-Thuillier, Bastian; Pérez-Testor, Carles (Frontiers in Psychology, 2025)
IntroductionRelationships are often the focal point of life and can have a positive or a negative impact on a child's or adolescent's development, thus understanding the traits of healthy dating relationships may benefit wellbeing during this period of life and into adulthood.MethodsIn this transversal study, a sample of 65 adolescents between 10 and 19 years of age were recruited from schools in Araucanía and metropolitan regions of Chile during 2023, and they were distributed into 10 focus groups stratified by gender and age. A qualitative methodology with a phenomenological approach was used. Content análisis was performed stratified by age group (10–14 years, 15–19 years) and gender identity.ResultsInformation was obtained from adolescents about what they considered a healthy relationship, making distinctions between different types of unhealthy relationships and capturing subtleties about what they considered protective and risk factors. The adolescents were not more consumers of information; they required commitment and support in their development processes.DiscussionListening to their own voice could help generate solutions that made more sense to them. In the view of an adolescent, the formation of romantic couples was a fundamental and important issue that should be considered in public policies that promote health and prevent dating violence and its consequences.